2017
DOI: 10.18203/2320-1770.ijrcog20174436
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal and fetal outcomes in gestational diabetes mellitus diagnosed either by oral glucose tolerance test or diabetes in pregnancy study group India

Abstract: Background: The optimal strategy for screening and diagnosis of Gestational Diabetes Mellitus (GDM) is still controversial and elusive. There is possibility of difference in maternal and fetal outcome depending on the diagnostic method used. This study throws light on the efficacy of two screening tests “Oral Glucose Tolerance Test’’ and “Diabetes in Pregnancy Study Group India” and to know maternal and fetal outcome in pregnancy complicated by GDM in Indian setting.Methods: Depending on the diagnostic method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Similar findings were noted on comparing the incidence of preeclampsia in GDM patients of both the groups with a p value of 1. In a study conducted by Sinha et al, 10 22% of the DIPSI and 26% OGTT group had hypertensive disorders as comorbidity in their study. Similar to our study, this study also showed no significant difference in both the groups when the parameter hypertensive disorders was compared and an equal predictive value of GDM pregnancies complicated by hypertensive disorders was found by both the tests.…”
Section: Discussionmentioning
confidence: 74%
“…Similar findings were noted on comparing the incidence of preeclampsia in GDM patients of both the groups with a p value of 1. In a study conducted by Sinha et al, 10 22% of the DIPSI and 26% OGTT group had hypertensive disorders as comorbidity in their study. Similar to our study, this study also showed no significant difference in both the groups when the parameter hypertensive disorders was compared and an equal predictive value of GDM pregnancies complicated by hypertensive disorders was found by both the tests.…”
Section: Discussionmentioning
confidence: 74%